Penerimaan Pasien Terhadap Layanan Pendaftaran Online Rawat Jalan di RSUD Wonosari dengan Metode UTAUT-2 - Rahmawati, Erlyna Dwi; Wigati, Putri Asmita; Kusumastuti, Wulan (Jurnal Riset Kesehatan Masyarakat, 2023)
RSUD Wonosari made an innovative WhatsApp-based online registration to overcome the problem of long waiting at the registration counter. This innovation was launched in January 2020 but in 2022 the user coverage has not yet reached the target. So a study was conducted on factors related to patient acceptance of online registration services. This research was conducted quantitatively using the cross-sectional method with 376 respondents in March - May 2023 who used the online outpatient registration service at Wonosari Hospital. The data analysis used is the Chi square test. The results showed that performance expectations (p=0.001) and effort expectations, social influence, supporting conditions, motivation, price values, and habits (p=0.000) were factors that had a relationship with patient acceptance of the online registration system with a correlation coefficient between 0.176 -0.577. There is a very weak relationship between effort expectancy and performance expectancy, a weak relationship between social influence and facilitating conditions, and a relatively strong relationship between motivation; price value; and habits with online registration system patient acceptance at Wonosari Hospital.